Impact Literacy Environment to Competence Community Environment in Pekanbaru City, Riau Province, Indonesia - Alvi, Ria Rizkia; Wahyudin, Uyu; Ardiwinata, Jajat Sudrajat; Robandi, Babang (Universitas Negeri Padang, 2025)
This study aims to analyze community environmental literacy, environmental competence, and the influence of environmental literacy on environmental competence. This study focuses on comprehensively assessing the environmental literacy of residents through four dimensions: environmental values, environmental responsibility, perception of environmental problems, and environmental behavioral skills. Similarly, the environmental competence of the community is evaluated through three dimensions: cognitive, affective, and methodological competence. The method used is quantitative with an ex post facto approach. Data from 65 valid surveys collected through an online questionnaire in Pekanbaru City reveal that the level of environmental literacy and environmental competence of the community is generally high, but their performance is relatively lower in dimensions such as environmental behavioral skills, environmental responsibility, and methodological competence. Further analysis shows a positive correlation between the four dimensions of environmental literacy and environmental competence. In particular, environmental behavioral skills and environmental responsibility play an important role in influencing environmental competence. Environmental literacy plays an important role in improving the community's ability to sort and process waste, while encouraging environmentally conscious behavior. Improving environmental competence through literacy has implications for sustainable development.